China's Growing Influence on Asian Financial Markets - Arslanalp, Serkan (IMF Working Papers; Working Paper, 2016)
This paper finds that financial spillovers from China to regional markets are on the rise. The main transmission channel appears to be trade linkages, although direct financial linkages are playing an increasing role. Without an impact on global risk premiums, China's influence on regional markets is not yet to the level of the United States, but comparable to that of Japan. If China-related shocks are coupled with a rise in global risk premiums, as in August 2015 and January 2016, spillovers to the region could be significantly larger. Over the medium term, China's financial spillovers could rise further with tighter financial linkages with the region, including through the ongoing internationalization of the renminbi and China's capital account liberalization.